The evolution of the main indicators of agriculture in the North-East Region of Romania - Victor Olteanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
In the article, we watched developments in the last 10 years, for the region of North-East of Romania, in the following areas: available land, technical-material base of agriculture, the agricultural area, agricultural crop Production, Livestock and crop production, livestock and farm animal animals a few inputs in agriculture: chemical fertilizers, plant protection treatments.
Keywords: 330; available land; improvements to land; crop production and cattle breeding